Kritik Sastra Feminisme dalam Cerpen Luh Sekar lan Satuané Rikala Ujané Bales Tusing Dadi Tanggehang - Ramadhana, Muhamad Rizky Rafli; Rai Putra, Ida Bagus; Antara, Nala (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research focuses on analyzing the female characters in Putu Supartika's short story,